Fasti Ecclesiæ Sarisberiensis: or, A calendar of the Bishops, Deans, Archdeacons, and members of the Cathedral body at Salisbury, from the earliest times to the present - Jones, W. H. Rich (Brown, 1879)
v. 1. 1. A history of the Episcopate, with a complete list of bishops. 2. The archdeacons of the diocese of Sarum.